Physical activity of 7-10 year-old primary schoolchildren in northern region - Busheva, Z.I. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to profile the daily/ weekly physical activity of the northern primary schoolchildren sample. Methods and structure of the study. We sampled for the study the 1-4-year (7-10 years old) primary schoolchildren (n=1342) qualified with the main health group from the Surgut and Nefteyugansk cities and Surgut Province in the Khanty-Mansi Autonomous Yugra area, whose daily/ weekly physical activity was rated using pedometers. The primary test data in movement numbers (locomotor units) were processed to produce empirical curves i.e. the daily/ weekly physical activity profiles. The physical activity profiles were found dependent on the individual living conditions, sports trainings and school studies. Based on the physical activity data analysis, the sample was grouped into the low, moderate, high and excessive physical activity ranks/ subgroups, with the relevant locomotor units limits. Results and conclusion. Our study of the 7-10-year-olds’ ​​daily/ weekly physical activity profiles in the Khanty-Mansi Autonomous Yugra area found a few regularities. On the whole, the daily/ weekly physical activity rating tests are recommended for research as they give stable data, conditional on gender-unspecific daily regimen being stable enough (with scheduled sports trainings, school physical activity classes and other studies without absenteeism). The study grouped the sample into the low, moderate, high and excessive physical activity / functionality ranks/ subgroups, with every of them tested with its specific daily/ weekly physical activity profiles. Our correlation analysis found the daily/ weekly physical activity being gender-specific, with the boys groups showing significantly higher physical activity.